2002
DOI: 10.1021/jf020160p
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiles of the Mycotoxin Zearalenone and of the Growth Promoter Zeranol in Urine, Liver, and Muscle of Heifers

Abstract: A group of five heifers were fed for 84 days with 2 kg of zearalenone-contaminated oats (1370 microg/kg) resulting in an average daily intake of 2740 microg of zearalenone per animal. In a parallel experiment five heifers were implanted with two 25 mg zeranol pellets, one at the beginning of the study and one after 42 days, and fed with 2 kg of "blank" control oats (79 microg/kg, daily intake = 158 microg). A third group of five animals were also fed with 2 kg of "blank" oats and served as control. Urine sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
65
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 21 publications
7
65
0
Order By: Relevance
“…A smaller number of studies have attempted to characterize residues of synthetic hormones in beef products [88,[96][97][98]. One study successfully measured hormone residues in these products, finding fractions of ppb residues in the liver, kidney, and muscle tissue of cattle implanted with E2 and TBA [88].…”
Section: Residue Determination Via Food Animal Feeding Studies and Rementioning
confidence: 99%
See 1 more Smart Citation
“…A smaller number of studies have attempted to characterize residues of synthetic hormones in beef products [88,[96][97][98]. One study successfully measured hormone residues in these products, finding fractions of ppb residues in the liver, kidney, and muscle tissue of cattle implanted with E2 and TBA [88].…”
Section: Residue Determination Via Food Animal Feeding Studies and Rementioning
confidence: 99%
“…One study successfully measured hormone residues in these products, finding fractions of ppb residues in the liver, kidney, and muscle tissue of cattle implanted with E2 and TBA [88]. Most other studies examined beef tissue for residues of zeranol, and never found concentrations above quantitation limits [96,97]. One older study that lacked a clear description of its analytical methods looked at beef liver, kidney, and muscle tissue for a suite of hormones (E2, MGA, progesterone, TBA, testosterone, and zeranol) and found no measurable residues [98].…”
Section: Residue Determination Via Food Animal Feeding Studies and Rementioning
confidence: 99%
“…IN limit of the physiological clearance period and the slaughter time of 60-70 days are necessary to wait in these countries. Moreover, residues of the anabolic agents in the ralgro applied animals are investigated using the sensitive analysis techniques (3,22,25,30), and then the permition for the consumption of the meat is given in these at the 35 countries. However, zeranol levels must be zero level in the tissue of Ralgro applied animals.…”
Section: Diccussion and Conclusionmentioning
confidence: 99%
“…A simple and rapid analytical methods were established for detection of anabolic agent. residues in tissues,faeces and urine samples of food producing animals (3,22,25,30).…”
Section: Diccussion and Conclusionmentioning
confidence: 99%
“…This mycotoxin is found in the grains of several monocotyledons, including pasture grasses. Due to their agonistic effects on the estrogenic receptor, ZEN and its metabolites exhibit distinct estrogenic and anabolic properties in several animal species which have several effects on the reproductive system (Kleinova et al 2002;Fink-Gremmels and Malekinejad 2007;Minervini and Dell'Aquila 2008). Several approaches for protecting animals from the toxic effects of mycotoxins, including both pre-and post-harvested products, have been conducted (Awad et al 2010).…”
mentioning
confidence: 99%